Strategies and Challenges in Introducing Shariah Financial Institutions to Students of Yannah Wittaya School Thailand - Mira Dipa; Rahmayati Rahmayati (International Conference on Islamic Economic (ICIE), 2026)
This research aims to analyze the strategies and challenges in introducing Islamic financial institutions to elementary school students at Yannah Wittaya School, Southern Thailand. The research uses a descriptive qualitative approach. Data collection was conducted thru in-depth interviews, participatory observation, and documentation. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing, with data validity ensured thru source and method triangulation. The research results show that the management of financial institutions is carried out thru systematic stages of planning, implementation, reporting, and supervision. Budget preparation is done participatively. Additionally, the practice of school financial management, which includes planning, implementation, reporting, and supervision systematically, also serves as a learning medium to instill values of accountability and transparency in students. However, the implementation of this program faces various challenges, including the limited competence of teachers in the field of sharia finance, limited integration into the formal curriculum, minimal learning resources and institutional support, as well as the low public understanding of the concept of sharia finance. Thus, the introduction of Islamic financial institutions at the elementary school level requires a synergy between innovative pedagogical strategies and sustainable institutional support to build Islamic financial literacy from an early age.